Respuesta :

remember, you can do anything to an equation as long as you do it to both sides


we can do a subsitution

y=x+6

y=-7x-10

since y=x+6, we can subsitute x+6 for y in the other equation

y=-7x-10

x+6=-7x-10

add 7x to both sides

8x+6=-10

minus 6 from both sides

8x=-16

divide both sides by 8

x=-16/8=-2


the valu eof x that satisfies both equations is x=-2

y = x + 6

y = -7x - 10

---

Solve for x in the first equation. Subtract y and x from both sides.

-x = 6 - y

Divide both sides by -1.

x = -6 + y

---

Plug x into the second equation.

y = -7(-6 + y) - 10

Distribute -7 inside the parentheses.

y = 42 - 7y - 10

Combine like terms.

y = 32 - 7y

Add 7y to both sides.

8y = 32

Divide both sides by 8.

y = 4

---

Plug 4 for y into the first equation.

4 = x + 6

Subtract 6 from both sides.

x = -2

---

Your answer is -2; x = -2 satisfies both equations.